1995
DOI: 10.1016/0092-8674(95)90518-9
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a paired domain-DNA complex at 2.5 å resolution reveals structural basis for pax developmental mutations

Abstract: The 2.5 A resolution structure of a cocrystal containing the paired domain from the Drosophila paired (prd) protein and a 15 bp site shows structurally independent N-terminal and C-terminal subdomains. Each of these domains contains a helical region resembling the homeodomain and the Hin recombinase. The N-terminal domain makes extensive DNA contacts, using a novel beta turn motif that binds in the minor groove and a helix-turn-helix unit with a docking arrangement surprisingly similar to that of the lambda re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
311
0
2

Year Published

1997
1997
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(327 citation statements)
references
References 46 publications
14
311
0
2
Order By: Relevance
“…2c) How does this mutation affect 5aCON binding? The Arg-128 residue may stabilize the protein-DNA interaction by directly contacting DNA, which is consistent with computer modelling (Xu et al 1995), while the mutated Cys residue may destabilize their interaction, for instance, by disulphide bond formation. To distinguish between these possibilities, we mutated the Arg-128 to residues other than Cys.…”
Section: Dna-binding Activity Of the C-terminal Subdomain Of Pax6 Paisupporting
confidence: 81%
See 1 more Smart Citation
“…2c) How does this mutation affect 5aCON binding? The Arg-128 residue may stabilize the protein-DNA interaction by directly contacting DNA, which is consistent with computer modelling (Xu et al 1995), while the mutated Cys residue may destabilize their interaction, for instance, by disulphide bond formation. To distinguish between these possibilities, we mutated the Arg-128 to residues other than Cys.…”
Section: Dna-binding Activity Of the C-terminal Subdomain Of Pax6 Paisupporting
confidence: 81%
“…The former has generally been considered to be important for specific DNA-binding (Chalepakis et al 1991;Treisman et al 1991). Recent X-ray structural analysis of paired has revealed that these subdomains contain helix-turn-helix motifs resembling the Hin recombinase, and are separated by a b-turn, and that the NTS and the b-turn make contacts with DNA (Xu et al 1995). In contrast to the other paired domain-containing proteins, however, both NTS and CTS of the Pax6 paired domain are suggested to have distinct DNA-binding activities (Epstein et al 1994b).…”
Section: Introductionmentioning
confidence: 99%
“…Top : schematic representation of the structure of the paired domain with the PAI and RED subdomains ; α-helical regions as described by Xu et al [10] are indicated. Bottom : all the oligonucleotides used in this study are aligned to the Pax-8 consensus sequence defined previously [11,12].…”
Section: Figure 1 Model Of the Pax-8 Prd Domain-c-sequence Interactiomentioning
confidence: 99%
“…Several studies have demonstrated that the Prd domain consists functionally of two distinct subdomains [8,9]. The crystal structure resolution of the Prd domain of the paired protein bound to DNA has also demonstrated the presence of two structurally independent subdomains, each containing a helix-turn-helix motif, joined by a linker region [10]. Recently, the N-and Cterminal subdomains have been named PAI and RED respectively [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation